Programa de monitoramento de parâmetros básicos da qualidade da água para consumo humano: proposição para um campus universitário - Oliveira, Emanuelly Kelly Gomes de (Universidade Federal Rural do Semi-Árido, 2021)
According to the Annex of Ordinance GM/MS No. 888/2021, all water intended for human consumption, collectively distributed through a collective alternative water supply system or solution, must be subject to water quality control and surveillance. In 1990s, the National Water Quality Surveillance Program for Human Consumption (Vigiagua) was instituted, consisting of a set of actions continuously adopted by public health authorities in the three spheres of management of the SUS, with the main goals of promoting population health, prevent waterbone diseases and other harms to health. Oriented in the use of Vigiagua as one of the technical-scientific bases for its development, the present paper aimed to propose a program for monitoring five basic parameters of water quality for human consumption at UFERSA campus Mossoró and, based on this, to present a diagnosis monitoring. The paper was executed in two main stages: (a) proposing a program for monitoring basic parameters of water quality for human consumption at UFERSA campus Mossoró and (b) preparing a diagnosis of monitoring the basic parameters of water quality for human consumption based on results obtained in previous researches. From the steps mentioned, it was possible to elaborate a program consisting of objectives, goals, indicators and methodological sheets, as well as to present a diagnosis of the monitoring of the basic parameters of water quality for human consumption for the institution. In the diagnosis, results were identified for 20 indicators related to the first sampling in building reservoirs and drinking fountains, including: sampling; analyzed parameters for physical-chemical and microbiological parameters; formally analyzed in compliance or not for the parameters; and provocation to clean building reservoirs and drinking fountains. From this, it is observed the proportion of buildings with the first sampling of water for human consumption carried out for building reservoirs (Indicator 1.1) and drinking fountains (Indicator 2.1), of 71.43 and 72.92%, respectively. Regarding the percentages analyzed for the turbidity parameters (Indicators 3.1 and 6.1), total coliforms / E. coli (Indicators 4.1 and 7.1) and free residual chlorine (Indicators 5.1 and 8.1), results of 75.48% were observed for reservoirs buildings and 70.97% for drinking fountains. A company in the program not proposed in the context of access to drinking water stands out. Notwithstanding to water quality, such as monitoring are essential to meet this component
Keywords: Plano de amostragem; Potabilidade; Diagnóstico; Reservatório predial; Bebedouro; Sampling plan; Potability; Diagnosis; Building reservoir; Drinking fountain; ENGENHARIAS::ENGENHARIA CIVIL